Concentrated Ownership of Indonesian Listed Companies as a Determinant of Stock Price Crash Risk - Putri Tamala; Arief Wibisono Lubis (Green Publisher Indonesia, 2025)
This study examines the relationship between ownership concentration and stock price crash risk in Indonesian publicly listed companies. In emerging markets like Indonesia, ownership is often concentrated in the hands of a few major shareholders, raising questions about information asymmetry and governance vulnerabilities. Using panel data from non-financial firms listed on the Indonesia Stock Exchange between 2014 and 2023, this study applies a quantitative approach with crash risk proxied by negative coefficient skewness (NCSKEW) and down-to-up volatility (DUVOL). Ownership concentration is measured as the combined shareholding of the top three shareholders in each firm. The results show that ownership concentration has a consistently positive but statistically insignificant relationship with stock price crash risk. These findings suggest that concentrated ownership, while prevalent in Indonesia, does not necessarily lead to greater downside risk. Instead, firm-specific characteristics such as profitability, liquidity, maturity, and external factors like the COVID-19 crisis may play a more decisive role. This study contributes to the growing literature on corporate governance in emerging markets by challenging commonly held assumptions about the risk implications of blockholder control.